2018
DOI: 10.1007/s00018-018-2903-z
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of ribosomal histidyl hydroxylases in cell biology, physiology and disease

Abstract: Hydroxylation is a novel protein modification catalyzed by a family of oxygenases that depend on fundamental nutrients and metabolites for activity. Protein hydroxylases have been implicated in a variety of key cellular processes that play important roles in both normal homeostasis and pathogenesis. Here, in this review, we summarize the current literature on a highly conserved sub-family of oxygenases that catalyze protein histidyl hydroxylation. We discuss the evidence supporting the biochemical assignment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 82 publications
(178 reference statements)
1
37
0
Order By: Relevance
“…A similar investigation into published JMJD6 substrates was also unable to confirm other proposed targets and biochemical activities beyond lysyl hydroxylation [123], including a reported histone arginyl demethylase activity [124]. In fact, initial assignments of histone demethylase activity (or declaration of KDM activity even in the absence of evidence), is a theme among the JmjC-only sub-family of 2OG-oxygenases (as discussed in [16,17,111]) (e.g. MINA, NO66, JMJD4, and JMJD7).…”
Section: Activity Assignment Controversymentioning
confidence: 94%
See 1 more Smart Citation
“…A similar investigation into published JMJD6 substrates was also unable to confirm other proposed targets and biochemical activities beyond lysyl hydroxylation [123], including a reported histone arginyl demethylase activity [124]. In fact, initial assignments of histone demethylase activity (or declaration of KDM activity even in the absence of evidence), is a theme among the JmjC-only sub-family of 2OG-oxygenases (as discussed in [16,17,111]) (e.g. MINA, NO66, JMJD4, and JMJD7).…”
Section: Activity Assignment Controversymentioning
confidence: 94%
“…In fact, TET2 is one of the most commonly mutated genes in AML [110]. For other 2OG-oxygenases however, particularly those in the JmjC-only sub-family, the picture is less clear [17,111]. In the case of arginyl hydroxylase JMJD5, for example, multiple studies have described both pro-and antitumourigenic functions.…”
Section: Og-oxygenases: Disease Mediatorsmentioning
confidence: 99%
“…The involvement of the JMJD-type demethylases in human physiology and diseases has been well documented, for instance, in the development, metabolic diseases, inflammation, and various types of cancer [3,4]. JMJD10/MINA53 belongs to a phylogenetically distinct group, known as the "JmjC-only" 2-oxoglutarate (2OG)-oxygenase subfamily, as it has a JmjC domain, which is capable of catalyzing protein hydroxylation (and demethylation via hydroxylation reaction) in a 2OG-dependent oxygenase manner and has no other immediate functional domains [5]. An investigation of biochemical activity revealed that JMJD10 has hydroxylation activity toward Rpl27a [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports suggest the overexpression of JMJD10/MINA53 in multiple cancers such as colorectal, lung, esophageal, glioblastoma, lymphoma, cholangiocarcinoma, gingival squamous cell carcinoma, neuroblastoma, liver, pancreatic, multiple myeloma, breast, and gastric cancer [5,10,[18][19][20][21][22][23][24][25][26]. An intricate role has also been described for JMJD10/MINA53, as overexpression may not always correlate with poor patient prognosis [5]. Supposedly, JMJD10/MINA53 might have opposing roles at different stages of tumorigenesis as it exhibits a growth-promoting role in early cancer but a tumor suppressor role in the later stages of the disease [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation